Science of the Secondary : An atlas of the everyday- No.13 (Atelier HOKO, 2022)
Atelier HOKO (2002) is an independent research lab that focuses on the study of the growing disengagement between people, things and space. Founded by Alvin Ho and Clara Koh. Science of the Secondary is an inquisitive approach towards uncovering implicit conditions that exist in our experience of the everyday. When speaking of the term 'secondary', we are referring to conditions and sensations that human beings are not conscious of in their day-to-day interaction with things and the immediate surroundings. Accumulating this rich and boundless field of knowledge, the research hopes to draw upon a renewed sensibility towards living,l with much excitement and freshness.
English
Keywords: N4390-5098 Visual Arts. Exhibitions